2014
DOI: 10.1002/pon.3488
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to mental health service use and preferences for addressing emotional concerns among lung cancer patients

Abstract: Objective This study examined barriers to mental health service use and preferences for addressing emotional concerns among lung cancer patients (N=165) at two medical centers in the midwestern United States. Methods Lung cancer patients completed an assessment of anxiety and depressive symptoms, mental health service use, barriers to using these services, and preferences for addressing emotional concerns. Results Only 45% of distressed patients received mental health care since their lung cancer diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 42 publications
2
50
1
Order By: Relevance
“…A noted reason people may not seek care or fully participate in care is the stigma surrounding the label of mental illness the perceived judgment it brings from others . It has also been shown that social support and cohesion in neighborhood settings may reduce the need to seek care among people without mental disorders . We considered how living with other adults as opposed to being the only adult in the household would be related to seeking care but there was no clear association.…”
Section: Discussionmentioning
confidence: 94%
“…A noted reason people may not seek care or fully participate in care is the stigma surrounding the label of mental illness the perceived judgment it brings from others . It has also been shown that social support and cohesion in neighborhood settings may reduce the need to seek care among people without mental disorders . We considered how living with other adults as opposed to being the only adult in the household would be related to seeking care but there was no clear association.…”
Section: Discussionmentioning
confidence: 94%
“…Some patients may not consider psychological counseling and some may avoid it due to perceived stigmas [84]. The development of efficient screening techniques will be necessary to rapidly assess patient needs and referral [85,86].…”
Section: The Psychoeducation Gapmentioning
confidence: 99%
“…Factors that have been identified to correlate with HSB among cancer survivors include: (a) perceived need for psychosocial services and support; (b) environmental conditions; (c) physical problems; and (d) psychological problems. First, perceived need for psychosocial services has been reported as a significant predictor to engage in HSB, whereas cognitive denial of one's own problems has been reported as a barrier (Dilworth, Higgins, Parker, Kelly, & Turner, ; Kumar et al., ; Matsui, Hirai, Shokoji, & Tokuyama, ; Mosher et al., ; Steginga et al., ). Second, environmental conditions, such as accessibility to service, cost of service, scheduling issues, and a lack of service‐related information, all contribute to HSB (Dilworth et al., ; Kumar et al., ; Matsui et al., ; Mosher et al., ).…”
Section: Current Models Of Ptg and Hsbmentioning
confidence: 99%
“…First, perceived need for psychosocial services has been reported as a significant predictor to engage in HSB, whereas cognitive denial of one's own problems has been reported as a barrier (Dilworth, Higgins, Parker, Kelly, & Turner, ; Kumar et al., ; Matsui, Hirai, Shokoji, & Tokuyama, ; Mosher et al., ; Steginga et al., ). Second, environmental conditions, such as accessibility to service, cost of service, scheduling issues, and a lack of service‐related information, all contribute to HSB (Dilworth et al., ; Kumar et al., ; Matsui et al., ; Mosher et al., ). Third, physical problems, including bodily conditions, time since the diagnosis, sex, and age of patients, explain the likelihood of HSB (Grande, Myers, & Sutton, ; Matsui et al., ; Mosher et al., ).…”
Section: Current Models Of Ptg and Hsbmentioning
confidence: 99%
See 1 more Smart Citation